Expression of an Expansin Is Associated with Endosperm Weakening during Tomato Seed Germination - Chen, Feng (American Society of Plant Physiologists, 2000)
Expansins are extracellular proteins that facilitate cell wall extension, possibly by disrupting hydrogen bonding between hemicellulosic wall components and cellulose microfibrils. In addition, some expansins are expressed in non-growing tissues such as ripening fruits, where they may contribute to cell wall disassembly associated with tissue softening. We have identified at least three expansin genes that are expressed in tomato (Lycopersicon esculentum Mill.) seeds during germination. Among these, LeEXP4 mRNA is specifically localized to the micropylar endosperm cap region, suggesting that the protein might contribute to tissue weakening that is required for radicle emergence. In gibberellin (GA)-deficient (gib-1) mutant seeds, which germinate only in the presence of exogenous GA, GA induces the expression of LeEXP4 within 12 hours of imbibition. When gib-1 seeds were imbibed in GA solution combined with 100 μm abscisic acid, the expression of LeEXP4 was not reduced, although radicle emergence was inhibited. In wild-type seeds, LeEXP4 mRNA accumulation was blocked by far-red light and decreased by low water potential but was not affected by abscisic acid. The presence of LeEXP4 mRNA during seed germination parallels endosperm cap weakening determined by puncture force analysis. We hypothesize that LeEXP4 is involved in the regulation of seed germination by contributing to cell wall disassembly associated with endosperm cap weakening.